A rationalized roman spelling system for the Indian languages without diacritical marks for use in certain applied areas - Ganeshsundaram PC (Journal of All India Institute of Speech and Hearing, 1970)
In this paper a Roman Spelling System for Indian Languages has been outlined, for use in special areas of application. A Speech Therapist, for example, who has to keep a written record of the speech of a patient, before, during and after therapy, at present finds it difficult to do so: firstly, because the use of the International Phonetic Alphabet, with its extra symbols and diacritical marks, requires too much patience and practice as a phonetician or linguist. Secondly, the therapist may be able to handle only one or two, Indian Language scripts, but may have to deal with patients speaking different languages. His familiarity with the 26 letters of the Roman alphabet, and the way they are combined in the proposed system to write his own language, makes it possible for him to note down words spoken in any other Indian language